Marketing Concept in the Function of Croatian Seaport Business Operation Improvement - Jurčević, Marinko; Skoko, Božo; Madunić, Perica (Promet - Traffic&Transportation, 2006)
The application of the scope of marketing concept in modemmarket conditions of business operation is obligatory. Therole of marketing, as a business philosophy, is in the end unavoidablefor the improvement of business operation. It is impossibleto do business in market conditions and not to applybasic marketing rules. Therefore, the solution for the improvementof operation of Croatian seaports should be soughtthrough the systematic application of the scopes of marketingconcept. Marketing mix should be applied to the system of businessoperation of Croatian seaports, with a breakdown of allunderlying marketing functions based on the results of a systematicmarket research, and through monitoring not only ofthe current status but also of market trends and forecasts, listeningto customer demands and trends in this particularbranch of industry. In addition to the improvement of the qualityof transport services, through the analysis of the price policyand by strengthening the logistics of port operation, particularattention should be focused towards the systematic applicationof all promotion mix elements aiming at strengthening the identityand the image of Croatian ports. In the end, such businessand marketing-like thinking should result in economic developmentand business prosperity not only of ports but of maritimetransport as well; in other words, by the prosperity of theentire transport activity, as a prerequisite for the economic developmentof the Republic of Croatia.